ADA APA DENGAN SUPERVISI PENDIDIKAN? - Ermi Sola (Universitas Islam Negeri Alauddin Makassar, 2018)
Education, in a simply meaning is making human being human, done through the process of learning. This process includes organizing to organize the environment of the class that will influence to their motivation of learning. In this case, the teacher is the main star to reach the goal of the meaningful learning. Among those activites the teachers should go through is supervision. Educational supervision is a service or an assistance given by the supervisor to the teachers in order to improve the quality of teaching and leaning,or a better teaching and learning situation. The principal at school is the supervisor for the teachers at school. The principal holds an important function in helping the teachers to improve their competencies and professionalism as well. In some schools, the supervisor make hard efforts to do their responsibility as supervisors, however, the result is still far from what it is expected. There is an image that the presence of the supervisor is just like a “monster” for the teachers. It is because of the attitude of the supervisor, such as insists his willingness, finds the teacher’s mistake, arrogant, and the other negative attitudes. These negative attitudes make the teachers feel inferior, powerless. This condition will contribute to a negative influence on the teacher’s motivation in exploring their creativity in teaching.